Upaya Penanggulangan Tindak Pidana Penyalahgunaan Narkotika oleh Anak di Wilayah Hukum Polresta Padang - Saputra, Widi; Yoserwan, Yoserwan; Suryani, Nilma (Dinasti Research, 2025)
Law enforcement cannot be carried out repressively because the juvenile justice system must prioritize the principle of child protection. This is especially true given the increasing number of cases, as evidenced by the police, and the number of cases occurring among them. This research problem is formulated below: How are efforts to prevent drug abuse by children in the Padang Police jurisdiction? This research method uses empirical juridical data. According to the research results, the Padang Police have implemented various structured prevention efforts. Prevention efforts are carried out through the